Iconography and Use of Urine in the History of Art - Colón Fraile, José Antonio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
We studied how the urinating action and the use of the own urine have been used as an element of artistic expression in different art throughout history disciplines. This tour was organized by subject indexes, from the simplest to the most complex images semiotically. Contemporary art deserved special attention by incorporating the use of the body and its fluids as examples of human fears and obsessions, characterized the appearance of urine by its radicalism and gender affiliation.